Nanoindentation measurement of core–skin interphase viscoelastic properties in a sandwich glass composite - Cao, Dongyang; Malakooti, Sadeq; Kulkarni, Vijay N.; Ren, Yao; Lu, Hongbing (Mechanics of time-dependent materials, 2021)
Debonding at the core–skin interphase region is one of the primary failure modes in core sandwich composites under shear loads. As a result, the ability to characterize the mechanical properties at the interphase region between the composite skin and core is critical for design analysis. This work intends to use nanoindentation to characterize the viscoelastic properties at the interphase region, which can potentially have mechanical properties changing from the composite skin to the core. A sandwich composite using a polyvinyl chloride foam core covered with glass fiber/resin composite skins was prepared by vacuum-assisted resin transfer molding. Nanoindentation at an array of sites was made by a Berkovich nanoindenter tip. The recorded nanoindentation load and depth as a function of time were analyzed using viscoelastic analysis. Results are reported for the shear creep compliance and Young’s relaxation modulus at various locations of the interphase region. The change of viscoelastic properties from higher values close to the fiber composite skin region to the smaller values close to the foam core was captured. The Young’s modulus at a given strain rate, which is also equal to the time-averaged Young’s modulus across the interphase region was obtained. The interphase Young’s modulus at a loading rate of 1 mN s −1 was determined to change from 1.4 GPa close to composite skin to 0.8 GPa close to the core. This work demonstrated the feasibility and effectiveness of nanoindentation-based interphase characterizations to be used as an input for the interphase stress distribution calculations, which can eventually enrich the design process of such sandwich composites.